Kinerja Pelayanan Publik Pemkot Surabaya Menurut Persepsi Masyarakat (Survey Pada Dispenduk Dan Puskemas) - Sudaryati, Erina (AKRUAL: JURNAL AKUNTANSI, 2012)
AbstractThis study aims to analyze the performance of Local Government Task Force related to services provided Surabaya public/ community as intended by Permendagri 73/2009. And to know the correspondence between the performance of services with the expectation or level of use of public interest services Surabaya Local Government Unit according to the index specified by KepMenpan No. 25/KEP/M.PAN/2/2004, Measurement of the dimensions of service quality is the 14 indicators specified in the questionnaire KepmenPan which were translated into 33 subindikator. The population in this study were all community care service users SKPD selected, the Office of Population and Civil serving the needs of birth certificates and service records related to identity issues and health centers (one selected health centers in the suburbs, namely Eastern Surabaya). While samples taken accidental sampling, ie respondents who can be found by the researchers. Results showed that administration of the health center service is good but still can be improved and Dispenduk still not satisfactory.